2020
DOI: 10.3390/biom10030419
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Fatty Acid Contents in Major Lipid Classes of Seven Salmonid Species from Siberian Arctic Lakes

Abstract: Long-chain omega-3 polyunsaturated fatty acids (LC-PUFA) essential for human nutrition are mostly obtained from wild-caught fish. To sustain the LC-PUFA supply from natural populations, one needs to know how environmental and intrinsic factors affect fish fatty acid (FA) profiles and contents. We studied seven Salmoniformes species from two arctic lakes. We aimed to estimate differences in the FA composition of total lipids and two major lipid classes, polar lipids (PL) and triacylglycerols (TAG), among the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 60 publications
(99 reference statements)
1
14
0
Order By: Relevance
“…Species of genus Salvelinus , collected in diverse water bodies and in aquaculture, and sample sizes are given in Table 2 . Although feeding habits of these species were well known from the literature [ 22 , 45 , 46 , 47 ], the stomach contents of some specimens were taken for microscopic analyses to check their food items ( Table 2 ), and for fatty acid (FA) analysis (see below).…”
Section: Methodsmentioning
confidence: 99%
“…Species of genus Salvelinus , collected in diverse water bodies and in aquaculture, and sample sizes are given in Table 2 . Although feeding habits of these species were well known from the literature [ 22 , 45 , 46 , 47 ], the stomach contents of some specimens were taken for microscopic analyses to check their food items ( Table 2 ), and for fatty acid (FA) analysis (see below).…”
Section: Methodsmentioning
confidence: 99%
“…Despite the fact that neural organs have the highest lipid contents and are the most energy-demanding tissues in animals, our current knowledge about energy flows in aquatic food webs is primarily derived from studies on fish muscle and liver tissues (Volk & Kiffney, 2012;Kainz et al, 2017;Sushchik et al, 2018). Previous research indicated that FA in neutral lipids (NL) of fish muscles, such as triacylglycerols (TAG), reflect those from the diet, while FA in the polar lipids (PL) of fish muscles are driven by taxonomy (Iverson 2009;Sushchik et al, 2020). Total lipids and TAG contents vary among fish organs (Tocher & Harvie, 1988;Budge et al, 2006;Hong et al, 2014) and thus different organs may vary in correspondence to dietary FA.…”
Section: Introductionmentioning
confidence: 99%
“…A reduced visual performance (Bell et al, 1995 ) or learning ability (Lund et al, 2014 ) of fish due to LC-PUFA-poor diets can reduce feeding success, predator avoidance (e.g., escape latency, swimming speed) and other behavioral traits, e.g., schooling behavior (Ishizaki et al, 2001 ). Despite the fact that neural organs have the highest lipid contents and are the most energy-demanding tissues in animals, our current knowledge about energy flows in aquatic food webs is primarily derived from studies on fish muscle and liver tissues (Volk & Kiffney, 2012 ; Kainz et al, 2017 ; Sushchik et al, 2018 ). Previous research indicated that FA in neutral lipids (NL) of fish muscles, such as triacylglycerols (TAG), reflect those from the diet, while FA in the polar lipids (PL) of fish muscles are driven by taxonomy (Iverson 2009 ; Sushchik et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, when the level of fattening increases in a fish, most of that fat is deposited in muscles, as TAG, to be an energy reserve. Thus, when FLC increases, fat deposits increase, TAG content increases and PL, together LCPUFA, is diluted [21].…”
Section: Heritability Of Fatty Acid Profilementioning
confidence: 99%
“…This is likely due to marine fish showing a limited ability to convert C18 FA into LCPUFA of n6 and n3 series [19,20]. In addition, while triacylglycerols (TAG) are in fat deposits, and usually contain MUFA (C16-C18); polar lipids, in membrane cells are composed mainly of phospholipids that accumulate LCPUFA [21]. An FLC increase is related to a higher amount of fat deposits and, concurrently, a higher proportion of TAG and MUFA and a lower proportion of polar lipids and LCPUFA.…”
Section: Introductionmentioning
confidence: 99%